2018
DOI: 10.1111/pan.13474
|View full text |Cite
|
Sign up to set email alerts
|

A simple care bundle to reduce unplanned admission rate for day case pediatric circumcision

Abstract: Summary Background An electronic review of unplanned day case admission rates in our hospital demonstrated an average annual rate for pediatric circumcision of 2%‐3% in recent years with high levels of perioperative strong opiate use. This lay above target unplanned admission rates (<2%) set out by the Royal College of Anaesthetists for day case surgery. A targeted quality improvement initiative was undertaken to improve patient flow through the pediatric day case surgery unit for elective circumcision. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Improving postoperative outcomes is a key area of interest for pediatric perioperative teams. Both enhanced recovery after surgery (ERAS) pathways and individual care bundle implementation have been employed to improve perioperative pediatric surgical outcomes. Reducing postoperative pain through targeting perioperative analgesic strategies is often a key component of such initiatives .…”
Section: Discussionmentioning
confidence: 99%
“…Improving postoperative outcomes is a key area of interest for pediatric perioperative teams. Both enhanced recovery after surgery (ERAS) pathways and individual care bundle implementation have been employed to improve perioperative pediatric surgical outcomes. Reducing postoperative pain through targeting perioperative analgesic strategies is often a key component of such initiatives .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is scarce literature regarding its use in pediatrics, especially in common urologic procedures such as circumcisions. Recent studies have shown that the unexpected admission rate for pediatric circumcision ranges from 2-3%, likely due to uncontrolled pain and PONV [11]. In another pediatric study, over half of parents reported their child experienced moderate to severe pain postoperatively [12].…”
Section: Discussionmentioning
confidence: 99%